Tipologi Politik Luar Negeri Indonesia Di Era Reformasi - Bambang Wahyu Nugroho (Jurnal Hubungan Internasional, 2013)
In the limited capacity of post-independence economic and military, various implementation of Indonesia’s foreign policies also be welcomed and got strong support from the power of the masses. But in the course of history, due to elitism in the Soeharto era, made foreign policy to be elitisized. Influence from people muted. The policies were run almost personally by President Suharto so that Indonesia’s foreign policy became uninstitutionalized. The changes of political system in the Reformasi era (reforms) since the fall of President Suharto created opportunities to reformulate and to institutionalize Indonesia’s foreign policy. Meanwhile, during the first decade of Reform era in Indonesia (1998-2008) world political scene has undergone many changes and dynamics that presents opportunities and challenges toward Indonesia’s foreign policy, particularly the transformation of economic globalization and international issues. Ambiguity of Indonesia’s foreign policy profile at the beginning of the Reformasi era became an intellectual challenge, namely how to explain the “profile” that often be simplified as just “no-profile”. Reforms provides an opportunity to the spirit of populism to back in, however the implementation of Indonesia’s foreign policy sometimes seems elitist. It’s a challenge for scientific analysis. Therefore, this work also specifically describes the factors forming the profile of implementation of RI’s foreign policy in the era of the Reform.